The role of abrasive particle size on erosion characteristics of stainless steel. (March 2019) - Nguyen, Q.B.; Nguyen, D.N.; Murray, R.; Ca, N.X.; Lim, C.Y.H.; Gupta, M.; Nguyen, X.C.
Abstract: Understanding the erosion characteristics in oil and gas equipment and abrasive transportation is of vitally important to implement the engineering design and subsequently prevent failures. In this study, an in-house erosion test facility was designed and built up and its performance was tested through studying the size effect of abrasive sand particle on the erosion behaviour of a commonly used stainless steel material in the oil exploitation field. The experimental results reveal that the erosion rate (kg/impact), the depth of erosion as well as the surface roughness increased while the width of wear scar decreased with the increasing of particle size. In addition, it's interesting to observe the shape of erosion scar changing from "W" to "U" shape when the particle size became bigger. Further, four main types of erosion mechanisms involved in the erosion process, namely, plastic deformation induced indentation, ploughing, cutting and sliding, and correlation between the erosion characteristics and microstructure is discussed. Highlights: The best erosion rate presentation would be mass loss per particle impact. The erosion rate, depth, and surface roughness increased while the width of wear scar decreased with the increasing of particle size. The shape of the wear scar changed from "W" to "U" shape when the abrasive particle size increased. Erosion mechanisms were plastic deformation induced indentation, ploughing, cutting and sliding.